Flood response capacity in socially vulnerable sectors of the Felix Osores Sotomayor delegation of the municipality of Queretaro - Hernández Guerrero, Juan; Ruíz Magaña, Martha Patricia; Rivera Godínez, María Fernanda (Acta Universitaria, 2022)
The recurrent and dangerous floods in the municipality of Queretaro are accompanied by the response of the government and the affected population, but such efforts have failed to mitigate or solve the problem, especially in socially vulnerable sectors. This paper analyzes the capacity to respond to floods in socially vulnerable sectors of the Felix Osores Sotomayor delegation of the municipality of Queretaro. The procedure consisted of identifying flood zones through documentary compilation, elaborating a social vulnerability index with multicriteria analysis, and determining the capacity to respond through a semi-structured survey. A total of 37 flood-prone sites and three priority zones with differences in social vulnerability were identified; moreover, it was found that the response capacity is based on individual and neighborhood actions and strategies, while the government responds with transitory assistance and discursive prevention. This study concludes with information for decision making to reduce flood risk.